2015
DOI: 10.1016/j.ijome.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Numerical performance analysis of acoustic Doppler velocity profilers in the wake of an axial-flow marine hydrokinetic turbine

Abstract: a b s t r a c tThe use of acoustic Doppler current profilers (ADCPs) for the characterization of flow conditions in the vicinity of both experimental and full scale marine hydrokinetic (MHK) turbines is becoming increasingly prevalent. The computation of a three dimensional velocity measurement from divergent acoustic beams requires the assumption that the flow conditions are homogeneous among all beams at a particular axial distance from the instrument.In the near wake of MHK devices, the mean fluid motion is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…When utilising D-ADPs for turbulence analysis, consideration of these varying scales is required [26,27]. Doppler noise is an inherent feature of the acoustic Doppler measurement technique, and correction methods have been employed in this work as described in Section 3.5 [28,29].…”
Section: Summary Of the Acoustic Doppler Profiling Techniquementioning
confidence: 99%
“…When utilising D-ADPs for turbulence analysis, consideration of these varying scales is required [26,27]. Doppler noise is an inherent feature of the acoustic Doppler measurement technique, and correction methods have been employed in this work as described in Section 3.5 [28,29].…”
Section: Summary Of the Acoustic Doppler Profiling Techniquementioning
confidence: 99%
“…The generation of the current data is based on two further standard assumptions [16], which are: Assumption 1: At each depth the current is constant and homogenous. Assumption 2: There is no vertical component to the current velocity.…”
Section: Currentsmentioning
confidence: 99%
“…Another source of error in ADP measurements is the beam misalignment in the instrument [15]. It has been demonstrated that the beam misalignment from its nominal beam angle can cause velocity errors [16], with Woodgate and Holroyd suggesting that the actual beam angle relative to vertical can deviate by 1 • or 2 • [17].…”
Section: Introductionmentioning
confidence: 99%
“…The MeyGen project in Scotland [12] is among the pioneering projects in which extracting tidal energy from tidal streams becomes operational and is also connected to the electric grid. In comparison, most other efforts have been largely focused on the earlier stage of tidal energy development, such as characterizing available tidal energy resources using computational models and testing MHK devices in the laboratory and at representative field-testing sites [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%